Combination of nanoparticle-based therapeutic vaccination and transient ablation of regulatory T cells enhances anti-viral immunity during chronic retroviral infection. Issue 1 (December 2016) - Knuschke, Torben; Rotan, Olga; Bayer, Wibke; Sokolova, Viktoriya; Hansen, Wiebke; Sparwasser, Tim; Dittmer, Ulf; Epple, Matthias; Buer, Jan; Westendorf, Astrid
Abstract Background Regulatory T cells (Tregs) have been shown to limit anti-viral immunity during chronic retroviral infection and to restrict vaccine-induced T cell responses. The objective of the study was to assess whether a combinational therapy of nanoparticle-based therapeutic vaccination and concomitant transient ablation of Tregs augments anti-viral immunity and improves virus control in chronically retrovirus-infected mice. Therefore, chronically Friend retrovirus (FV)-infected mice were immunized with calcium phosphate (CaP) nanoparticles functionalized with TLR9 ligand CpG and CD8+ or CD4+ T cell epitope peptides (GagL85–93 or Env gp70123–141 ) of FV. In addition, Tregs were ablated during the immunization process. Reactivation of CD4+ and CD8+ effector T cells was analysed and the viral loads were determined. Results Therapeutic vaccination of chronically FV-infected mice with functionalized CaP nanoparticles transiently reactivated cytotoxic CD8+ T cells and significantly reduced the viral loads. Transient ablation of Tregs during nanoparticle-based therapeutic vaccination strongly enhanced anti-viral immunity and further decreased viral burden. Conclusion Our data illustrate a crucial role for CD4+ Foxp3+ Tregs in the suppression of anti-viral T cell responses during therapeutic vaccination against chronic retroviral infection. Thus, the combination of transient Treg ablation and therapeutic nanoparticle-based vaccination confers robust and sustained anti-viral immunity.